2022
DOI: 10.1039/d2qo01281b
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical C–H functionalization to synthesize 3-hydroxyalkylquinoxalin-2(1H)-ones via quinoxalin-2(1H)-ones and aldehydes

Abstract: Direct C3-functionalized of quinoxalin-2(1H)-ones are a convenient way to develop new and sustainable strategies, which are important for natural product and drug modification. Here, we report an electrocatalytic C-H activation...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Based on the control experiments and related literature, 3–6,15,16 a plausible mechanism was proposed using 1a and 2b as the model substrates (Scheme 5). Firstly, intermediate 3ab′ is formed via the Friedel–Crafts reaction between 1a and 2b catalyzed by B(C 6 F 5 ) 3 ·H 2 O.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the control experiments and related literature, 3–6,15,16 a plausible mechanism was proposed using 1a and 2b as the model substrates (Scheme 5). Firstly, intermediate 3ab′ is formed via the Friedel–Crafts reaction between 1a and 2b catalyzed by B(C 6 F 5 ) 3 ·H 2 O.…”
Section: Resultsmentioning
confidence: 99%
“…The yield of 3a decreased to 67% in the absence of water, and the yield of 3a decreased to 58% without ferrocene (Table , entries 11 and 12). The screening of the redox catalysts indicated that ferrocene was the best catalyst (Table S1, entries 15–17) . Undoubtedly, an electric current is necessary for this reaction (Table , entry 13).…”
Section: Resultsmentioning
confidence: 99%
“…As an important factor affecting the reaction, the electrolyte was screened. When CH 3 OH, THF, DMF, DMSO, DCE, and 22), which may be due to the side reaction. 46 Therefore, the best suitable current for the system was the constant current of 6.0 mA.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This method could synthesize 2-arylquinazolinone more efficiently in a shorter time, but expensive transition metals were used during the reaction process. In recent years, electrocatalysis has caught the eyes of many researchers due to its virtues of simple operation, cleanliness, and efficiency. In 2022, Li and his colleagues developed a protocol for electrochemical arylation of quinoxalines with arylhydrazine hydrochlorides under mild conditions (Scheme d) . Electrocatalysis can synthesize 2-arylquinoxaline cleanly and efficiently under mild conditions, but it is still necessary to add electrolytes to the reaction solution to promote the reaction, and the electrolyte cannot be recycled, causing environmental pollution.…”
Section: Introductionmentioning
confidence: 99%